Preliminary study on the effect of gamma radiation on the furniture carpet beetle anthrenus flavipes LeConte (Coleptera: Dermestidae) - Bassim Sh. Hamad; Mohammed Z. Khalaf; Huthaifa M. Jumaa; Nawal H. Yasseen; Ayad A. Al-Taweel (مجلة بغداد للعلوم)
Preliminary study on the possibility od using gamma radiation to induce sexual sterility in males of the furniture carpet beetle A. flavipes was carried out as a part of programme aiming to use SIT in controlling this pest.